PENGARUH KOMPENSASI, PELATIHAN KARYAWAN DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA DI PT MATAHARI DEPT STORE ARTOS MALL MAGELANG - Sivensius Taek; Syeh Assery (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to analyze the effect partially and simultaneously between compensation, job training and competence on work productivity using primary data from questionnaires. The population in this study were all employees of MSD Artos Mall Magelang and the research sample was determined by probability sampling method with simple random technique to obtain 50 sample.The results of multiple linear regression analysis obtained a significance value of F test of 0,000 < 0,05. These results sshow that simultaneously compensation, job training and competence have a significant effect on work productivity. While the results of the partial the obtained the correlation coefficient of the compensation variable 4,346 with a sig value of 0,000 < 0,05, job training variable 0,520 with a sig value of -0,048 >0,05 and the competency variable 1,294 with a sig value of 0,000 < 0,05. So that partially compensation and competence variables have a significant effect on job training productivity and have no effect on work productivity.